2018
DOI: 10.1108/ijlls-01-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the borders of the local

Abstract: Purpose: In this paper, we present how experiences gained from a theory informed lesson study -learning study -in regard to a specific learning goal can be shared and used by other teachers in new contexts.Design: A group of teachers worked together in a cyclic, iterative process of planning, evaluating and revising teaching. The aim was to provide possibilities for grade 2 and 3 students to become familiar with negative numbers. The teacher group draw the conclusion that the students needed to be able to diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Kullberg's study suggests that the identified critical aspects are critical to develop a capability and specific knowing, thus they are features of the object of learning. The same is indicated by Runesson, Lövström, and Hellquist (2018). They tested critical aspects for "realizing the existence of negative numbers" identified in a learning study in Grade 2 in eight classes.…”
Section: Putting the Results Of Learning Study To The Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Kullberg's study suggests that the identified critical aspects are critical to develop a capability and specific knowing, thus they are features of the object of learning. The same is indicated by Runesson, Lövström, and Hellquist (2018). They tested critical aspects for "realizing the existence of negative numbers" identified in a learning study in Grade 2 in eight classes.…”
Section: Putting the Results Of Learning Study To The Testmentioning
confidence: 99%
“…When the results from the pre-and post-assignments were analysed, it was found that the improvement of students' performance in the "replication lesson" reflected the improvement in the learning study lesson. Runesson et al (2018) suggest not only that identifying critical aspects and embedding them as patterns of variation affect students' learning, but also that they are relevant beyond the local context.…”
Section: Putting the Results Of Learning Study To The Testmentioning
confidence: 99%